A methods engineering study on Vida International Fashion Inc. - Carandang, Regine; Dela Cruz, Carrel; Liquigan, Boots (Diliman, Quezon City College of Engineering, 2003)
Vida International Fashion Inc. manufactures ready to wear and made to order garment items. Its profit is centered mostly on it RTW products. This study is focused on improvement of current methods of the company for the purpose of yielding higher productivity, efficiency, and effectiveness of all aspects of its manufacturing process. Data gathering and method analysis are conducted through plant visits where necessary inquiries are done. Various Method Engineering tools are utilized in the study to help the group achieve its objectives in this study. There were 19 problems verified. However, the main effect of these problems is the addition of cost to production of finished goods. Currently, the company is experiencing financial difficulties and the problem of addition of costs to production is significant because this directly and indirectly contributes to the said problem. The owner had also pointed out his main concerns in the production area of his company and these are the productivity and consistency of his workers. The group is tasked to generate plausible alternative or solution to the problems to be addressed. A minimum of one a maximum of four alternatives were formulated. Value Engineering was used to weigh the worth and practicability of each alternative. The analysts focused on alternatives that would give a low cost solution to the problems and this factor is given the largest weight in considering an alternative. The analysts had also considered alternatives that would not reduce cost but increase productivity as a whole and decrease worker fatigue, which also contributes to less efficiency. After generating and evaluating the alternatives, these will be subject for implementation based on the discretion of the company. Tools discussed in the Methods Engineering class proved to be useful in this study. A knowledge and understanding of the concepts and principles of Methods Engineering is of great significance especially in understanding how real life systems work.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis